ANALISIS PRODUCT POSITIONING PEMUTIH WAJAH POND’S FAIR & LOVELY DI SURABAYA - Rina Dewi (Fakultas Ekonomi Universitas 45 Surabaya, 2018)
This research examined about product positioning analysis of X face bleach in Surabaya. The growing competition in the cosmetic whitening business needs to get the attention of PT Unilever as the licensee of X brand to do the positioning for its brand in face bleaching product category to face the competition. The existence of a society that over communications, the company must create a position in the minds of prospects. Companies should create products with important attributes in accordance with the consumer needs selected by the company, then communicated to consumers to form a perception or to get a response from consumers. According to Walker, Boyd & Larreche (1992: 203) that positioning can be done in two ways: physical product positioning and perceptual product positioning. One way to assess the current position of a product offered against a competitor is based on how the supply is compared to a set of objects, ie physical characteristics. For perceptual product positioning, consumers usually do not want to be bothered with information about the physical characteristics of the product, consumers do not buy physical products but they buy the benefits of the product. Consumers evaluate the product on the basis of what it does rather than what it is. The analysis model used in this study is a model adopted from